Metoda wyodrębniania odtwarzalnych konstrukcji werbo-nominalnych języka rosyjskiego z korpusów tekstowych - Fedorushkov, Yury; Dzienisiewicz, Daniel (Studia Rossica Posnaniensia, 2019)
The article describes an extraction method of Russian verbal-nominative structures from electronic texts with the use of grammatical annotation and regular expressions syntax. The stages of the retrieval process are outlined. The list of extracted structures can be subsequently verified for the presence of reproducible units (phrasems).